Upregulation of Plasmid Genes during Stationary Phase in Synechocystis sp. Strain PCC 6803, a Cyanobacterium - Berla, Bertram M. (American Society for Microbiology, 2012)
We analyzed DNA microarrays to identify highly expressed genes during stationary-phase growth of Synechocystis sp. PCC 6803. Many identified genes are on endogenous plasmids, with copy numbers between 0.4 and 7 per chromosome. The promoters of such genes will be useful for synthetic biology applications with this phototrophic host.